Die St. Nicolai (Dominikaner) Kirche Jul. Greth. - Greth, Julius Gotthard Beniamin (1824-1903) (Verlag von Theodor Bertling in Danzig ; Druck v. C.G. Kanter, 1856)
Przedstawia widok fasady kościoła św. Mikołaja przed przebudową w 1860 r.